Waterborne polyurethane single-ion electrolyte from aliphatic diisocyanate and various molecular length of polyethylene glycol (eXPRESS Polymer Letters, 2007)
The waterborne polyurethane (WPU) dispersions from the reaction of cycloaliphatic diisocyanates [4,4’-methylenebis(cyclohexyl isocyanate) (H12MDI) and isophorone diisocyanate (IPDI)] and polyethylene glycol (PEG) with various molecular lengths were synthesized using our modified acetone process. Differetial scanning calorimeter (DSC) and Fourier transform infrared spectroscopy (FTIR) were utilized to characterize WPU films for the behavior of their crystallinity and H-bonding of WPU films. The Tg value of WPU increases with increasing the molecular length of PEG, whereas the Tm of WPU decreases with increasing PEG length. Alternating current (AC) impedance experiments were performed to determine the ionic conductivities of WPU films. The WPU gel electrolytes exhibits an ionic conductivity as high as ~ 10-5 S/cm at room temperature.